Autorregulación y protagonismo en la crianza. La agencia en el modelo de crianza respetuosa en Argentina - Mantilla, María Jimena (2023)
In this paper, I interrogate the images of childhood in the model of respectful parenting from a sociological perspective. I am interested in problematizing the notion of agency in articulation with the new social studies of childhood. To this end, I describe the main characteristics that define respectful parenting from the perspective of its followers, and I focus on the example of complementary feeding where I delve into how it produces a view of babies which enhances their agency when it comes to managing the feeding process. This paper is based on previously conducted qualitative ethnographic research about the experiences of middle-class mothers whofollow this style of parenting in the city of Buenos Aires, Argentina.